산국 생균제 급여가 거세한우의 성장과 육질에 미치는 영향 - 이혁준; 조성래; 김동현; 아만눌라; 주영호; 양한술; 최인학; 문성실; 김삼철; H. J. Lee; S. L. Cho; D. H. Kim; et al. (농업생명과학연구, 2014)
본 연구는 산국 생균제가 비육후기 거세한우의 성장율과 육질에 미치는 효과를 조사하기 실시하였다. 거세한우 15두(565±17kg)를 시험구별 개시체중이 유사하도록 산국 생균제 무첨가구(CON), 농후사료의 0.2% 첨가구(LCB) 및 0.4% 첨가구(HCB)에 각 5두씩을 배치하고 150일간 사양시험을 실시하였다. 농후사료와 조사료를 8:2의 비율로 설정하고 생체중의 약 2.5%를 오전(8시)과 오후(5시)로 나누어 급여하였다. 미네랄 블록과 음수는 자유로이 섭취할 수 있도록 하였다. 사양시험 종료 후에는 모든 공시동물은 도축하여 도체특성을 조사하고 등심육을 채취하여 육질분석에 이용하였다. 개시체중과 종료체중은 처리구간 차이가 없었으나, 일당증체량, 사료섭취량 및 사료효율은 산국 생균제를 급여한 모든 시험구에서 대조구에 비해 개선되었다(p<0.05). 분 중 황화수소와 암모니아 가스는 시험구간 차이가 없었다. 신선육 관능평가에서 등심육의 육색은 산국 생균제를 급여한 시험구가 개선되었으나(p<0.05), 등심육의 물리화학적 특성과 기타 신선육 관능평가는 시험구간 차이가 없었다. 등심육의 지방산 조성은 산국 생균제를 급여한 시험구에서 C14:0과 C18:0 함량이 증가하였으며(p<0.05), HCB 시험구에서 C18:2n-6와 polyunsaturated fatty acid 함량은 HCB 시험구에서 가장 높게 나타났다(p<0.05). 따라서 비육후기 거세한우에 산국 생균제를 0.4% 수준으로 급여하는 것은 사료효율 개선, 육색 및 등심육 지방산 품질개선에 유리할 것으로 사료된다. This study was conducted to investigate the effect of Chrysanthemum boreale probiotics (CB) supplementation on growth performance and meat quality of Hanwoo steers. Fifteen (Body weight, 565±17kg) steers were allocated by body weight (BW) and assigned for 150 days to one of three treatments; 0 (Control, CON), 0.2% (Low CB, LCB) or 0.4% (High CB, HCB) of CB (DM basis) were supplemented to concentrate. Concentrate and rice straw with an 8:2 ratio was offered at 2.5% of BW and fed twice daily (08:00 and 17:00). Water and mineral-vitamin block were allowed in ad libitum. All steers were slaughtered at the end of feeding trial to measure carcass characteristics and meat quality. There were no differences in initial BW and final BW among treatments. However, daily gain, feed intake and feed efficiency in LCB and HCB were greater (p<0.05) than those in CON. The fecal emissions of H2S and NH3 gas were not affected by CB supplementation. Meat color in raw meat sensory score was greater (p<0.05) in all CB supplemented treatments than CON, while physicochemical characteristics and other sensory scores of longissimus muscle were not affected. The concentrations of C14:0 and C18:0 were greater in all CB supplemented treatments (p<0.05) than those in CON. Also, C18:2n-6 and polyunsaturated fatty acid concentrations were greatest (p<0.05) in HCB. In conclusion, 0.4% of CB supplementation could improve feed efficiency, meat color and muscle fatty acid quality of Hanwoo steers.